PENGARUH ORGANIZATIONAL COMMITMENT, WORK LIFE BALANCE, DAN WORKLOAD TERHADAP PERFORMANCE TENAGA KESEHATAN RUMAH SAKIT UMUM (RSU) MUHAMMADIYAH - Wijayanti, Alif Via Rahma; Chamidah, Siti; Purwaningrum, Titis (Jurnal Manajemen, 2024)
This research aims to find out how much influence organizational commitment have on the performance of health workers at RSU Muhammadiyah,, work life balance have on the performance of health workers at RSU Muhammadiyah, and workload have on the performance of health workers at RSU Muhammadiyah. The method used in this research is a quantitative research method. Research variable data was collected by distributing questionnaires to 70 respondents using probability sampling techniques with the simple random sampling method. The results of this research show that organizational commitment has a significant effect on performance, work life balance does not have a significant effect on performance, workload has a significant effect on performance. The R-Square value shows 70.8%, the remaining 29.2% is influenced by other variables not examined in this research.